An ionic liquid treatment and fractionation of cellulose, hemicellulose and lignin from oil palm empty fruit bunch. (15th June 2017) - Mohtar, Safia Syazana; Tengku Malim Busu, Tengku Nur Zulaikha; Md Noor, Ahmad Mujahid; Shaari, Norsalliana; Mat, Hanapi
Highlights: Cellulose, hemicellulose and lignin were successfully extracted from OPEFB. Only 73.71 and 82.94% wt. of cellulose and lignin were recovered, respectively. High recovery of hemicellulose (273.71% wt.) due to its impurities. [bmim][Cl] degraded after the fourth cycle. Abstract: This work reports on a complete isolation and characterization of lignocellulosic compounds from oil palm empty fruit bunch (OPEFB) by ionic liquid (IL) treatment and alkaline treatment processes. The fractionated lignocellulosic compounds were confirmed by FTIR and CP/MAS 13 CNMR analyses. The yield of the cellulose, hemicellulose and lignin fractions was 52.72 ± 1.50% wt., 27.17 ± 1.68% wt. and 16.82 ± 1.15% wt. with molecular weight of 1869 g/mol, 1736 g/mol and 2695 g/mol, and degradation temperature of 325.65 °C, 236.25 °C, and 201.40 °C, respectively. The SEM image illustrates the bundle-like fiber of cellulose fraction and smaller particle size of hemicellulose and lignin fractions with inconsistent shape. The XRD patterns depict the crystalline cellulose, amorphous lignin and partially amorphous hemicellulose fractions property. The IL could be recovered and reused with an overall recovery of 48% wt. after the fourth cycle.